Understanding Ourselves and Our World from the Multiplicity of World-Views: Perspectives in African Epistemological Relationality - Obinyan, Valentine Ehichioya; Ehimua, Faith Gloria (NIU Journal of Social Sciences, 2024)
The importance of epistemological relationality in understanding ourselves and our world has been the focus of recent attention in global academic scholarship. In times past, this has been monopolized by one or some cultures over others. However, the components of this relationality have not been exhaustively theorized from different philosophical perspectives, allowing specific Western philosophical conceptions to dominate the dimension of discuss in literatures on this subject. The impact of this has been cultural supremacy, racial relegation and deprivation. This research offers a theoretical analysis of the global connection and ontological background that informs various conceptualizations of ourselves and our world from African, Western and Eastern world-views and unloads its implication for a value driven and harmonious coexistence. It aims at broadening this conception in Western and Eastern traditions, while showing what precedes this reflection and highlighting with analysis, the multiple relational process of knowing this African ontological value. This research therefore adopts the hermeneutics and critical analysis methods. It argues that multiplicity of world-views is a reflection of relationality in the unique ways we conceptualize reality from cultural events even though in diverse and informal forms. It concludes that this multiplicity in learning and understanding ourselves and our world forms the rational foundation for a complementary interrelation and mutual respect in the world and Africa in particular. Keywords: African, Philosophy, Multiplicity, World-views, Epistemological, Relationality, Understanding ourselves, Complementary, Relation and Mutual Respect.